Exploring the emergence and impact of pentecostal movements in Nigeria (2025)
From time immemorial, Christianity has played a pivotal role in the spiritual rejuvenation of its adherents. The spiritual renewal has positively impacted the country in all ramifications, especially the mainline churches that laid the foundation of Christianity on Nigerian soil. Existing studies on the contributions of Christianity to society have focused mainly on the spiritual and psychological effort of the mainline churches, with little attention paid to the emergence and the impact of Pentecostal churches in Nigeria. The advent of Pentecostal movements in Nigeria, which began in the early 20th Century as a reform movement in the prominent churches of Africa, was a significant historical event. This paper adopts a historical method to elicit information on Pentecostal movements in Nigeria, bringing to the fore their historical context and interventions in the growth of African Christianity and their general influence on society. Our findings revealed that Pentecostal movements in Nigeria have, over the years, advanced the course of Christianity with their Creative liturgical ideas. Recommendations were made on how some excesses of Pentecostal churches would be put under check to ensure sanity in the movement.